AKTIVITAS ANTIJAMUR FRAKSI DAUN MANGKOKAN (Polyscias scutellaria) TERHADAP JAMUR TRICHOPHYTON RUBRUM - Rury Trisa Utami; Sri Hainil; Hesti Marliza; Hafizah, Hafizah (Nusantara Hasana Journal, 2026)
One of the natural ingredients that are often used as medicinal plants is mangkokan leaves (Polyscias scutellaria). Mangkokan leaves have the potential as an antifungal. Trichophyton rubrum is a fungus that infects human skin. The purpose of this study was to determine the antifungal activity of mangkokan leaf fractions (Polyscias scutellaria) against Trichophyton rubrum fungi. Fractionation was carried out using the liquid-liquid method using n-hexane, ethyl acetate and ethanol-water solvents. Testing was carried out using the disc paper diffusion method. The concentration of the fraction extract used was 600 µg/disk. The results showed that of the three fractions of mangkokan leaves (Polyscias scutellaria), the ethyl acetate fraction and the ethanol-water fraction had antifungal activity, while the n-hexane fraction did not have antifungal activity. Based on the research that has been done, it can be concluded that the fraction of mangkokan leaves (Polyscias scutellaria) has antifungal activity against Trichophyton rubrum fungus. Of the three fractions tested, the ethanol-water fraction has the highest antifungal activity with an average inhibition zone of 11.3 mm against Trichophyton rubrum fungus, the ethyl acetate fraction has an inhibition zone with an average of 4.5 mm while the n-hexane fraction has no inhibition zone. The three fractions have been compared with ketoconazole 30 µg/disk as a positive control and 10% DMSO as a negative control. From the comparison of fraction measurements against the positive control, the ethanol-water fraction is included in the strong category and the ethyl acetate fraction is included in the weak category.